Robust Foreground Removal for Hydrogen Intensity Mapping (HIM) Experiments - Podczerwinski, John (Proceedings of the Wisconsin Space Conference, 2023)
This paper describes work done to develop robust methods for foreground removal in hydrogen intensity mapping (HIM) experiments. In HIM, one measures the 21cm line from neutral hydrogen (HI), which in turn provides information about the distribution of matter in the universe. However, foreground emission from the milky way and extra-galactic sources must be removed in order to obtain useful results. Methods developed for removing these foregrounds either have not been thoroughly tested on realistic data, or perform poorly when the instrument is not precisely calibrated. The goal of the work here is to develop a method to remove foregrounds that works on realistic, imperfectly calibrated data.